Avaliação dos efeitos biológicos da fração polissacarídica SK5 isolada do fungo Ganoderma australe em macrófagos de camundongo swiss - Melo, Renan Henrique de (2014)
Ganoderma australe is a Basidiomycete species responsible for the delignification process of the organic matter known to cause "white rot" in certain species of trees. Cytochemical studies have shown that the cell wall of fungi polysaccharides has (13)- β-glucans, (16)-β-glucans type and other complex polysaccharides. Currently, it has been highlighted that the β-glucans are polysaccharides that produce higher effects as modulators of biological functions. In previous studies, the fungus G. australe has been studied regarding the composition of the cell wall polysaccharide. SK5 polysaccharide fraction was obtained after freeze-thawing of the aqueous extraction with KOH 5%. Monosaccharide composition of SK5 fraction revealed by Gas chromatography–mass spectrometry (GC-MS) showed glucose is predominant (81.3%), with presence of other sugars (mannose, arabinose, xylose, rhamnose, fucose and galactose) at concentration of less than about 3% each. The nuclear magnetic resonance of this fraction proved to be a β-glucan with glycosidic links (1→3)-β type and probably replaced in 4-O. In this study, the biological effect of SK5 polysaccharide fraction extracted from the fungus G. australe has been evaluated in vitro cell culture of peritoneal macrophages isolated from Swiss mice. The biological effect was assessed for toxicity and cell activation, nitric oxide, cytokines (TNF-α, IL-6), superoxide anion (production and scavenging capacity) and the ability to stimulate phagocytic activity. Cell viability was affected, with approximately 29% reduction with 1.0 mg / mL and 35.5% reduction with 2.5 μg/ml SK5. There was no change in nitric oxide production, TNF-α or superoxide anion concentrations between 0.1 μg/mL and 1.0 μg/mL. The scavenging ability of superoxide anion was also not detected. There was an increase in IL-6 by about 111% with 1.0 μg/mL. In regarding to phagocyte activity was increased in all concentrations examined obtaining 52.3% with 0.25 μg/mL of polysaccharide. The results indicate that (13)-β- glucan isolated from G.australe can be classified as biological response modifier (BRM).